Autologous platelet rich plasma versus corticosteroid injection for chronic plantar fasciitis: a prospective controlled randomized comparative clinical study - Upadhyay, Sachin; Damor, Vijendra (International Journal of Research in Medical Sciences, 2018)
Background: Primary objective was to evaluate and compare the effectiveness of autologous platelet rich plasma (PRP) and steroid injections in chronic cases of plantar fasciitis. Methods: The present study was a prospective cohort study; 140 consecutive patients with chronic plantar fasciitis were enrolled and randomized in two groups: One receives the Platelet rich plasma (PRP) therapy (study group) and another receiving corticosteroid injection (control group). The outcomes in both groups are then evaluate and compared using visual analogue scale (VAS) and American Orthopaedic foot and Ankle Society (AOFAS) scale at 1month, 3month and 6 month post injection. The level of significance was set at p <0.05. Results: Prospective data was collected of 140 heels. The average follow up duration was about 6 months. The score on VAS scale and AOFAS improved from base line for both group but the patients received PRP therapy had a statistically significant (p<0.05) reduction in pain and improved AOFAS score at last follow up. No adverse complications were reported. Conclusions: The result of present study showed that the PRP therapy has potential to reduce pain and improve the functional outcome in cases of chronic planter fasciitis. It was found to be more effective and significantly better than corticosteroid injection.